Fair and foul beyond the myths and paradoxes of sport - Eitzen, D. Stanley (Rowman & Littlefield Publishers, 2012)
"With revisions and updates throughout, the fifth edition of "Fair and Foul" explores America's love of sport and also it's darker side. Updates include further attention to how race, class, and gender relate to the uneven playing field in sports; a new discussion of sexuality as a divisive factor in sport; and numerous new case studies and examples"--